Method for constructing cathode-free battery current collector based on assistance of liquid metal template
By constructing a negative electrode-free battery current collector with the assistance of a liquid metal template and utilizing the lithiation characteristics of Ga2O3 seed crystal powder, the problem of uneven deposition of lithium ions on copper foil current collectors is solved, thereby improving the battery's lifespan and safety.
Patent Information
- Application Number
- CN202511046234.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-21
AI Technical Summary
In existing negative electrode-free battery systems, lithium ions are deposited unevenly on copper foil current collectors, which can easily lead to problems such as deposition layer detachment and dendrites piercing the separator, affecting the battery's lifespan and safety.
A liquid metal template was used to construct a current collector for a negative electrodeless battery. By preparing Ga2O3 seed crystal powder encapsulated in a spherical carbon shell, the affinity of the lithiation products of Ga2O3 for lithium ions was utilized to induce lithium ions to be uniformly deposited on a fixed mirror surface, preventing dendrite growth.
Uniform lithium-ion deposition was achieved, improving battery cycle life and safety, and significantly enhancing the performance of electrodeless lithium-ion batteries and solid-state batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for constructing a cathode-free battery current collector based on a liquid metal template, and belongs to the technical field of battery current collector manufacturing. Background Art
[0002] The structure of a commercial lithium-ion battery cell can be summarized as: anode current collector / anode / separator / cathode / cathode current collector, with the entire system immersed in a liquid electrolyte (e.g., copper / graphite / separator / lithium cobalt oxide / aluminum and copper / graphite / separator / lithium iron phosphate / aluminum systems). During charging, lithium ions extracted from the cathode diffuse through the electrolyte-soaked separator and then intercalate into the anode material (i.e., graphite). The discharge process proceeds in reverse. Currently, the energy density of commercial lithium-ion batteries is approaching the material's lithium storage limit. To achieve higher energy density, improvements in battery structure are essential. Ideally, if lithium ions extracted from the cathode could reversibly plate and strip (in the form of metallic lithium) from the copper current collector, a rechargeable lithium-ion battery with a copper / separator / cathode / aluminum structure could be assembled. Initially, such a battery contains no active anode material and is therefore referred to as an "anode-free rechargeable lithium-ion battery." By eliminating the need for an anode material, an anode-free system significantly reduces battery weight and volume. Due to the theoretical capacity of metallic lithium (3820mAh / cm 2 ) is graphite (372mAh / cm 2 Even taking into account the increase in thickness of the battery due to lithium deposition on the current collector when charging, the energy density of the negative electrode-free lithium-ion battery will still be significantly higher than that of the traditional lithium-ion battery, which makes it possible to increase the energy density (Wh / L) of the negative electrode-free lithium-ion battery by about 50% or more relative to the traditional lithium-ion battery.
[0003] The viability of anode-free battery systems depends on the reversibility of lithium deposition and stripping on the current collector. However, direct lithium deposition on copper foil, a current collector without lithium storage properties, can lead to problems such as uneven deposition, shedding of the deposited layer, and the formation of dendrites that pierce the separator. Summary of the Invention
[0004] In response to existing anode-free battery systems, which suffer from the problem of uneven deposition, shedding of the deposited layer, and formation of dendrites that pierce the diaphragm when lithium ions released from the positive electrode are directly deposited on the copper foil, the present invention provides a method for constructing an anode-free battery current collector based on a liquid metal template. Spherical carbon-shell-encapsulated Ga2O3 seed crystal powder is prepared using a liquid metal template. The spherical carbon-shell-encapsulated Ga2O3 seed crystal powder is mixed with a binder, polyvinylidene fluoride, and then slurried to obtain a slurry. The slurry is coated on the surface of the copper foil current collector to form an anode-free battery current collector. The anode-free battery current collector has excellent uniform lithium deposition induction capabilities and can prevent the growth of lithium dendrites, thereby improving the lifespan and safety of anode-free lithium-ion batteries and anode-free solid-state batteries. The present invention uses a spherical carbon-shell-encapsulated Ga2O3 seed crystal layer as an anode-free current collector. When used in anode-free lithium-ion batteries or anode-free solid-state batteries, the cycle life and safety of the batteries can be significantly improved.
[0005] A method for constructing a negative electrode-free battery current collector based on a liquid metal template, the specific steps are as follows: (1) adding liquid metal to an ethanol / deionized water mixed solvent, then adding polyvinyl pyrrolidone, and ultrasonically treating to obtain a liquid metal nanoparticle suspension; (2) adding a liquid metal nanoparticle suspension and resorcinol powder into a formaldehyde solution, and keeping the solution at a temperature of 20-50°C for 24-48 hours to obtain a polymer-coated liquid metal nanodroplet suspension; (3) The polymer-coated liquid metal nanodroplet suspension is freeze-dried at a temperature of -20 to 0°C for 24 to 48 hours to obtain a powder, and the powder is uniformly mixed with iron oxide to obtain a mixture; (4) The mixture is placed in a vacuum calcination at a temperature of 200-400 °C for 24-48 h to carbonize the polymer into a carbon shell, and then added to a concentrated acid solution to etch away excess liquid metal, cleaned, and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell; (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to prepare a slurry. The slurry is evenly coated on the surface of the copper foil current collector and vacuum dried to form a negative electrode-free battery current collector.
[0006] Preferably, the volume ratio of ethanol to deionized water in the ethanol / deionized water mixed solvent in step (1) is 1:1-8.
[0007] Preferably, the liquid metal in step (1) is metallic gallium or a gallium-based liquid metal alloy, the concentration of the liquid metal in the liquid metal nanoparticle suspension is 0.5-1.0 g / mL, and the solid-liquid ratio (g:mL) of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent is 0.2-2:100.
[0008] More preferably, the gallium-based liquid metal alloy is GaIn, GaSn, GaAl, GaInSn or GaInSnZn.
[0009] Preferably, in step (2), the solid-to-liquid ratio of the resorcinol powder, the formaldehyde solution, and the liquid metal nanoparticle suspension is g:mL:mL in a range of 10-50:200-500:100.
[0010] Preferably, the iron oxide in step (3) is Fe2O3 and / or Fe3O4.
[0011] More preferably, the mass ratio of the powder to the iron oxide in step (3) is 1:1-5.
[0012] Preferably, the concentrated acid solution in step (4) is one or more of concentrated sulfuric acid, concentrated hydrochloric acid, and concentrated nitric acid.
[0013] Preferably, the etching temperature in step (4) is 60-100° C., and the etching time is 20-48 hours.
[0014] Preferably, in step (5), the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 7-10:1, and the slurry viscosity is 60-600 Pa·s.
[0015] The present invention is based on the principle of using liquid metal template to assist in constructing anode-free battery current collector to improve the cycle life and safety of the battery: the basic principle is as follows: using the affinity of Ga2O3 and its lithiated products to lithium ions, gallium oxide is used as an inducer to induce lithium ions to deposit on a fixed (001) mirror surface. The details are as follows: In situ XRD experiments show that the phase transformation of Ga2O3 during lithium insertion and over-lithiation deposition is Ga2O3-Li x Ga2O3-Ga-Li x Ga-Li x Ga+Li; DFT calculations confirm that the binding energy of lithium ions in each stage is Ga2O3 (-2.01eV)<Li x Ga2O3(-2.21eV)<Ga(-2.43eV)<Li x Ga (-2.81eV); from the principle of chemical potential, this phase transition is a spontaneously induced phase transition with gradually increasing induction ability; therefore, this characteristic can be used to use Ga2O3 as an induction layer to induce lithium deposition to improve the coulombic efficiency. x Ga to Li x During the Ga+Li transformation, the excess lithium ions are in the Li xThe (001) crystal plane of Ga is preferentially deposited, which causes most of the lithium to be deposited in a spherical form, thus preventing lithium from growing in the form of dendrites, thereby reducing the risk of lithium batteries short-circuiting due to dendrite growth and improving battery safety.
[0016] The beneficial effects of the present invention are: (1) The present invention uses gallium-based liquid metal as a template for sphericity to prepare Ga2O3 seed crystals in a carbon shell, which can better obtain carbon-coated Ga2O3 with uniform size and excellent sphericity. As an induction layer for lithium deposition on a negative electrode-free current collector, the modified current collector has good electrolyte wettability. After being assembled into a battery, the Ga2O3 seed crystals covered with the current collector will uniformly induce lithium deposition on the entire copper foil surface, and the carbon in the shell plays a role in hindering and inhibiting the unlimited growth of lithium dendrites, achieving excellent battery performance in both half-cells and full cells. (2) The present invention modifies the copper foil current collector of lithium-ion batteries / solid batteries, and the process is completely integrated with the commercial process. If the material prepared by this method is used to mass-produce negative electrode-free batteries, the production process of the entire workshop can remain completely unchanged, and only the slurry ratio can be changed. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 XRD patterns of liquid metal Ga, liquid metal Ga nanodroplets, and quantitatively oxidized liquid metal Ga nanodroplets during the preparation process of Example 1; Figure 2 This is the SEM image of the nanodroplet of Example 1Ga; Figure 3 TEM image of carbon-coated Ga2O3 seed crystal prepared using Ga as template in Example 1; Figure 4 The wettability test results of the negative electrode-free battery current collector and the original copper foil current collector in Example 1 are shown. (a) is the current collector in this example, and (b) is pure copper foil. Figure 5 The critical current density test results of the liquid half-cell without negative electrode battery current collector in Example 2; Figure 6 The long cycle test results of the liquid full battery without negative electrode battery current collector in Example 2; Figure 7 TEM image of the carbon-coated Ga2O3 seed crystal prepared using GaIn as a template in Example 3; Figure 8 The long cycle test results of the solid-state half-cell without negative electrode battery current collector in Example 3; Figure 9 This is an SEM image of the carbon-coated Ga2O3 seed crystal prepared using GaInSn as a template in Example 3; Figure 10The solid-state full-battery rate performance + long cycle test results of the negative electrode-free battery current collector in Example 3; Figure 11 The long cycle test results of the solid-state full battery without negative electrode battery current collector in Example 4 are as follows; Figure 12 The following are photos of the uniform lithium deposition on the negative electrode-free battery current collector in Example 4, (a) is a photo of the morphology before deposition, and (b) is a photo of the morphology after deposition; Figure 13 Scanning electron microscope plane photos of the uniformly deposited lithium on the current collector of the negative electrode-free battery in Example 4, (a) the spherical lithium morphology after deposition using the current collector of this example, (b) the lithium dendrite morphology after deposition using copper foil as the current collector; Figure 14 These are scanning electron microscope cross-sectional photos of the uniformly deposited lithium on the current collector of the negative electrode-free battery in Example 4, (a) measurement of the cross-sectional coating thickness, (b) linear scanning route of the cross-sectional area, and (c) linear scanning result of the cross-sectional area. DETAILED DESCRIPTION
[0018] The present invention will be further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0019] Example 1: A method for constructing a negative electrode-free battery current collector based on a liquid metal template, the specific steps are as follows: (1) Liquid metal Ga was added to an ethanol / deionized water mixed solvent (the volume ratio of ethanol to deionized water was 1:1), and then polyvinyl pyrrolidone was added, and the mixture was ultrasonically treated and subjected to gradient centrifugation to obtain a liquid metal nanoparticle suspension, wherein the average particle size of the liquid metal nanoparticles was 150 nm; the concentration of liquid metal Ga in the liquid metal nanoparticle suspension was 0.5 g / mL, and the solid-liquid ratio of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent was g:mL 0.2:100; The XRD patterns of the liquid metal Ga, the liquid metal Ga nanodroplets and the quantitatively oxidized liquid metal Ga nanodroplets during the preparation process of this embodiment are shown in FIG. Figure 1 ,from Figure 1 It can be seen that at 30°C, no peaks appeared in liquid metal Ga and Ga nanodroplets, indicating that Ga is in a liquid amorphous phase; after being quantitatively oxidized by iron oxide, peaks of gallium oxide began to appear, proving that it was successfully oxidized; The SEM image of the liquid metal nanoparticle suspension of this embodiment is shown in FIG. Figure 2 ,from Figure 2 It can be seen that most of the liquid metal Ga presents a standard spherical morphology with a diameter between 0.5μm and 2μm; (2) adding a liquid metal nanoparticle suspension and resorcinol powder to a formaldehyde solution, and preserving the solution at 20°C for 48 hours to obtain a polymer-coated liquid metal nanodroplet suspension; the solid-liquid ratio of the resorcinol powder, formaldehyde solution, and liquid metal nanoparticle suspension is 10:200:100 g:mL:mL; (3) The polymer-coated liquid metal nanodroplet suspension was freeze-dried at -20°C for 24 h to obtain a powder, and the powder was mixed with iron oxides (Fe2O3 and Fe3O4) to obtain a mixture; the mass ratio of the powder, Fe2O3, and Fe3O4 was 8:1:1; (4) The mixture was placed in a vacuum calcination at 20 ° C for 48 h to carbonize the polymer into a carbon shell, and then added to a concentrated acid solution (concentrated hydrochloric acid with a mass concentration of 60%), and etched at 60 ° C for 48 h to remove excess liquid metal Ga. The mixture was then washed and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell; The TEM image of the carbon-coated Ga2O3 seed crystal prepared using Ga as a template in this embodiment is shown in FIG. Figure 3 ,from Figure 3 It can be seen that the inner shell structure can be clearly seen under transmission electron microscopy; the measured value of the lattice fringes (d=0.23nm) shows that the lattice spacing belongs to the (002) crystal plane of Ga2O3, proving that its interior is pure gallium oxide; (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to adjust the slurry to a viscosity of 100 Pa·s to obtain a slurry, and the slurry is evenly coated on the surface of the copper foil current collector by a coating machine, and vacuum dried to form a negative electrode-free battery current collector; the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 7:1; The wettability test results of the negative electrode-free battery current collector and the original copper foil current collector in this embodiment are shown in Figure 4 (a) is the electrode sheet prepared in this example, (b) is pure copper foil, Figure 4 It can be seen that the electrode sheet prepared in this embodiment has excellent wettability to the electrolyte, has almost no wetting angle, and can achieve a nearly 100% wetting effect; The test results of the liquid half-cell rate performance of the negative electrode-free battery current collector of this embodiment are shown in Figure 5 The prepared current collector was tested for performance by a third-party testing platform (CATL & Yunnan Liquid Metal Research Institute). The battery system is a lithium-ion battery organic ester liquid system, and the battery structure is a lithium-current collector symmetrical battery. The specific test conditions are: constant temperature dry room (25°C), constant current discharge voltage of -0.2V~0.2V, and constant current test current density of 0.25~20mA / cm 2The current collector prepared in this embodiment can withstand a higher current density, increasing the critical battery density to 14.0 mAh / cm 2 ; The long cycle test results of the liquid full battery without negative electrode current collector in this embodiment are shown in Figure 6 The prepared current collector was tested for performance by a third-party testing platform (CATL & Yunnan Liquid Metal Research Institute). The battery system is a lithium-ion battery organic ester liquid system, and the battery structure is a soft-pack full battery. The specific test conditions are: constant temperature dry room (25°C), constant current discharge voltage of 0.01V~1.5V, and constant current test current density of 1A / cm 2 The current collector prepared in this embodiment is used in a full battery system and can achieve 1000 charge and discharge cycles while still retaining 145 mAh / cm 2 capacity.
[0020] Example 2: A method for constructing a negative electrode-free battery current collector based on a liquid metal template, the specific steps are as follows: (1) Liquid metal GaIn was added to an ethanol / deionized water mixed solvent (the volume ratio of ethanol to deionized water was 1:2), and then polyvinyl pyrrolidone was added, and the mixture was ultrasonically treated and subjected to gradient centrifugation to obtain a liquid metal nanoparticle suspension, wherein the average particle size of the liquid metal nanoparticles was 100 nm; the concentration of liquid metal GaIn in the liquid metal nanoparticle suspension was 0.6 g / mL, and the solid-liquid ratio of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent was 1.5:100 g:mL; (2) adding a liquid metal nanoparticle suspension and resorcinol powder to a formaldehyde solution, and keeping the solution at 30°C for 40 h to obtain a polymer-coated liquid metal nanodroplet suspension; the solid-liquid ratio of the resorcinol powder, formaldehyde solution, and liquid metal nanoparticle suspension was 15:250:100 g:mL; (3) The polymer-coated liquid metal nanodroplet suspension was freeze-dried at -10°C for 32 hours to obtain a powder, and the powder was mixed with iron oxide (Fe2O3) to obtain a mixture; the mass ratio of the powder to Fe2O3 was 1:3; (4) The mixture was calcined in vacuum at 350°C for 12 h to carbonize the polymer into a carbon shell. The mixture was then added to a concentrated acid solution (95% concentrated sulfuric acid) and etched at 60°C for 40 h to remove excess liquid metal GaIn. The mixture was then cleaned and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell. The TEM image of the carbon-coated Ga2O3 seed crystal prepared using GaIn as a template in this embodiment is shown in FIG. Figure 7 ,from Figure 7 It can be seen that carbon shell-encapsulated Ga2O3 seed crystals were successfully synthesized, and the volume proportion of Ga2O3 seed crystals was about 20%; (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to adjust the slurry to a viscosity of 120 Pa·s to obtain a slurry, and the slurry is evenly coated on the surface of the copper foil current collector by a coating machine, and vacuum dried to form a negative electrode-free battery current collector; the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 8:1; The long cycle test results of the solid-state half-cell without negative electrode battery current collector in this embodiment are shown in Figure 8 The prepared current collector was tested for performance by a third-party testing platform (CATL & Yunnan Liquid Metal Research Institute). The battery system is a lithium-ion battery organic ester liquid system, and the battery structure is a soft-pack solid-state full battery. The specific test conditions are: constant temperature dry room (25°C), constant current discharge voltage of 0.01V~1.5V, and constant current test current density of 1A / cm 2 The current collector prepared in this embodiment is used in a full battery system and can achieve 3000 charge and discharge cycles while still retaining about 180 mAh / cm 2 capacity.
[0021] Example 3: A method for constructing a negative electrode-free battery current collector based on a liquid metal template, the specific steps are as follows: (1) Liquid metal GaInSn was added to an ethanol / deionized water mixed solvent (the volume ratio of ethanol to deionized water was 1:4), and then polyvinyl pyrrolidone was added, and the mixture was ultrasonically treated and subjected to gradient centrifugation to obtain a liquid metal nanoparticle suspension, wherein the average particle size of the liquid metal nanoparticles was 1000 nm; the concentration of liquid metal GaInSn in the liquid metal nanoparticle suspension was 0.8 g / mL, and the solid-liquid ratio of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent was 2:100 g:mL; (2) adding a liquid metal nanoparticle suspension and resorcinol powder to a formaldehyde solution, and keeping the solution at 40°C for 30 hours to obtain a polymer-coated liquid metal nanodroplet suspension; the solid-liquid ratio of the resorcinol powder, formaldehyde solution, and liquid metal nanoparticle suspension is 20:300:100 (g:mL:mL); (3) The polymer-coated liquid metal nanodroplet suspension was freeze-dried at -5°C for 40 h to obtain a powder, and the powder was mixed with iron oxide (Fe3O4) to obtain a mixture; the mass ratio of the powder to Fe3O4 was 1:4; (4) The mixture was calcined in vacuum at 350°C for 28 h to carbonize the polymer into a carbon shell. The mixture was then added to a concentrated acid solution (95% concentrated nitric acid) and etched at 80°C for 30 h to remove excess liquid metal GaIn. The mixture was then cleaned and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell. The SEM image of the carbon-coated Ga2O3 seed crystal prepared using GaInSn as a template in this embodiment is shown in FIG. Figure 9 ,from Figure 9 It can be seen that the carbon shell-encapsulated gallium oxide structure was successfully synthesized; (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to adjust the slurry to a viscosity of 330 Pa·s to obtain a slurry, and the slurry is evenly coated on the surface of the copper foil current collector by a coating machine, and vacuum dried to form a negative electrode-free battery current collector; the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 9:1; The solid-state full battery rate performance + long cycle test results of the negative electrode-free battery current collector of this embodiment are shown in Figure 10 The prepared current collector was tested for performance by a third-party testing platform (CATL & Yunnan Liquid Metal Research Institute). The battery system is a lithium-ion battery organic ester liquid system, and the battery structure is a soft-pack solid-state full battery. The specific test conditions are: constant temperature dry room (25°C), constant current discharge voltage of 0.01V~1.5V, and the current density of the constant current test of the rate is 0.1-0.2-0.5-1-2-1-0.5-0.2-0.1A / cm 2 , the current density parameter for long cycle is 1A / cm 2 The current collector prepared in this embodiment is used in an all-solid-state battery system and can achieve more than 1600 charge and discharge cycles while still retaining about 135 mAh / cm 2 capacity.
[0022] Example 4: A method for constructing a negative electrode-free battery current collector based on a liquid metal template, the specific steps are as follows: (1) Liquid metal GaInSnZn was added to an ethanol / deionized water mixed solvent (the volume ratio of ethanol to deionized water was 1:8), and then polyvinyl pyrrolidone was added, and the mixture was ultrasonically treated and subjected to gradient centrifugation to obtain a liquid metal nanoparticle suspension, wherein the average particle size of the liquid metal nanoparticles was 15 nm; the concentration of liquid metal GaInSnZn in the liquid metal nanoparticle suspension was 1.0 g / mL, and the solid-liquid ratio (g:mL) of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent was 2:100; (2) adding a liquid metal nanoparticle suspension and resorcinol powder to a formaldehyde solution, and preserving the mixture at 50°C for 24 hours to obtain a polymer-coated liquid metal nanodroplet suspension; the solid-liquid ratio of the resorcinol powder, formaldehyde solution, and liquid metal nanoparticle suspension was 20:200:100 (g:mL:mL); (3) The polymer-coated liquid metal nanodroplet suspension was freeze-dried at 0°C for 48 h to obtain a powder, and the powder was mixed with iron oxide (Fe3O4) to obtain a mixture; the mass ratio of the powder to Fe3O4 was 1:4; (4) The mixture was calcined in vacuum at 400°C for 10 h to carbonize the polymer into a carbon shell. The mixture was then added to a concentrated acid solution (30% by mass of concentrated hydrochloric acid) and etched at 100°C for 20 h to remove excess liquid metal GaInSnZn. The mixture was then washed and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell. (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to adjust the slurry to a viscosity of 600 Pa·s to obtain a slurry, and the slurry is evenly coated on the surface of the copper foil current collector by a coating machine, and vacuum dried to form a negative electrode-free battery current collector; the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 10:1; The long cycle test results of the solid-state full battery without negative electrode current collector in this embodiment are shown in Figure 11 The prepared current collector was tested for performance by a third-party testing platform (CATL & Yunnan Liquid Metal Research Institute). The battery system is a lithium-ion battery organic ester liquid system, and the battery structure is a soft-pack solid-state full battery. The specific test conditions are: constant temperature dry room (25°C), constant current discharge voltage of 0.01V~1.5V, and long cycle current density parameter is 2.0A / cm 2 The current collector prepared in this embodiment is used in an all-solid-state battery system and can achieve more than 5000 charge and discharge cycles while still retaining about 110 mAh / cm 2 capacity; The actual photo of the negative electrode-free battery current collector uniformly depositing lithium is shown in the figure. Figure 12 , (a) is the photo before deposition, (b) is the photo after deposition; Figure 12 It can be seen that the lithium is silvery white after deposition. From a plane perspective, the lithium is evenly distributed on the surface of the electrode. The scanning electron microscope plane photo of the uniform deposition of lithium on the current collector of the negative electrode-free battery in this embodiment is shown in Figure 13 , (a) the morphology of lithium deposited on the current collector of this embodiment, (b) the morphology of lithium deposited on the pure copper foil current collector of the comparative sample, from Figure 13 It can be seen that the lithium deposited by the current collector of this embodiment is spherical lithium deposition, while the lithium deposited by ordinary copper foil is in a dendritic state, which shows that the current collector of this embodiment can effectively prevent the growth of lithium dendrites and reduce the short circuit risk caused by lithium dendrites. The scanning electron microscope cross-sectional photograph of the uniform lithium deposition on the current collector of the negative electrode-free battery in this embodiment is shown in FIG. Figure 14, (a) measurement of lithium deposition cross-section thickness, (b) linear scanning route map of energy spectrum of deposition cross-section, (c) result map of energy spectrum; from Figure 14 It can be seen that the original current collector thickness is 20 microns, and the thickness of the lithium after deposition is 5 microns. From the cross-section, the deposition thickness is uniform and there are no vertical lithium dendrites; this further illustrates the inhibitory effect of the current collector of this embodiment on lithium dendrites, thereby improving the safety of the negative electrode-free battery.
Claims
1. A method for constructing a negative electrode-free battery current collector based on a liquid metal template, characterized in that: The specific steps are as follows: (1) adding liquid metal to an ethanol / deionized water mixed solvent, then adding polyvinyl pyrrolidone, and ultrasonically treating to obtain a liquid metal nanoparticle suspension; (2) adding a liquid metal nanoparticle suspension and resorcinol powder into a formaldehyde solution, and keeping the solution at a temperature of 20-50°C for 24-48 hours to obtain a polymer-coated liquid metal nanodroplet suspension; (3) The polymer-coated liquid metal nanodroplet suspension is freeze-dried at a temperature of -20 to 0°C to obtain a powder, and the powder is uniformly mixed with iron oxide to obtain a mixture; (4) The mixture is placed in a vacuum calcination at a temperature of 200-400 °C to carbonize the polymer into a carbon shell, and then added to a concentrated acid solution to etch away excess liquid metal, cleaned, and vacuum dried to obtain Ga2O3 seed crystal powder wrapped in a hollow carbon shell; (5) The Ga2O3 seed crystal powder wrapped in the hollow carbon shell is mixed with the binder polyvinylidene fluoride, and then N-methylpyrrolidone solution is added to prepare a slurry. The slurry is evenly coated on the surface of the copper foil current collector and vacuum dried to form a negative electrode-free battery current collector.
2. The method for constructing a negative electrode-free battery current collector based on a liquid metal template according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to deionized water in the ethanol / deionized water mixed solvent is 1:1-8.
3. The method for constructing a negative electrode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: In step (1), the liquid metal is metallic gallium or a gallium-based liquid metal alloy, the concentration of the liquid metal in the liquid metal nanoparticle suspension is 0.5-1.0 g / mL, and the solid-liquid ratio (g:mL) of polyvinyl pyrrolidone to the ethanol / deionized water mixed solvent is 0.2-2:
100.
4. The method for constructing a negative electrode-free battery current collector based on liquid metal template assistance according to claim 3, characterized in that: The gallium-based liquid metal alloy is GaIn, GaSn, GaAl, GaInSn or GaInSnZn.
5. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: In step (2), the solid-liquid ratio of the resorcinol powder, the formaldehyde solution and the liquid metal nanoparticle suspension is 10-20:200-300:100 in g:mL:mL.
6. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: In step (3), the iron oxide is Fe2O3 and / or Fe3O4.
7. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 6, characterized in that: The mass ratio of the step (3) powder to the iron oxide is 1:1~5.
8. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: The concentrated acid solution in step (4) is one or more of concentrated sulfuric acid, concentrated hydrochloric acid, and concentrated nitric acid.
9. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: In step (4), the etching temperature is 60-100°C and the etching time is 24-48 hours.
10. The method for constructing anode-free battery current collector based on liquid metal template assistance according to claim 1, characterized in that: In step (5), the mass ratio of the Ga2O3 seed crystal powder wrapped in the hollow carbon shell to the binder polyvinylidene fluoride is 7-10:1, and the slurry viscosity is 60-600 Pa·s.